Plan de exportación de joyas finas para la empresa Gruminep Cía. Ltda. provincia de El Oro - Espinoza Carranza, Dennis Xiomara (2015)
In a world where the production of jewelry is new, many opportunities for members of the value chain is open, for that reason this paper analyzes the feasibility of markets arise craftsmen for jewelry making based luxury gold in the US market, it should be noted that preference worldwide have these gems, they have been increased in a very fast way. USA is one of the most advanced markets where demand much of this product. This paper proposes a plan of export of luxury jewelry for the company GRUMINEP CIA. LTDA of the Province of El Oro, in order to producers export their products to the international market, contributing to foreign exchange earnings to the country and the use of sustainable raw materials. The export plan intended as a practical guide and easy to apply, since it contains all the techniques and tools necessary to market the gold luxury jewelry outward and achieve the expected return.